Discovering the true Schumpeter: New insights into the finance and growth nexus - Peter Bofinger; Lisa Geißendörfer; Thomas Haas; Fabian Mayer (University of Würzburg, Department of Economics, 2022)
Joseph A. Schumpeter is one of the most famous economists of the 20th century and the 'patron saint' of the finance and growth literature. We have discovered that the prevailing literature has, however, misinterpreted Schumpeter, which leads to puzzling empirical results and difficulties in explaining even fundamental relationships. We argue that this is due to a misrepresentation of the role of banks and liquidity creation and the role of household saving. After a critical discussion of the literature, we provide our own empirical analysis using a panel of 43 countries to explore the relationships between the important variables of the finance and growth literature. Our empirical analysis above all supports Schumpeter's view that credit growth supports GDP growth while saving is irrelevant for credit growth and GDP growth. In sum, a correct interpretation of Schumpeter helps to overcome the theoretical and empirical challenges which confront the prevailing literature.
Keywords: B20; B22; C10; E44; F30; F43; G21; O11; O16; O4; 330; Finance-growth nexus; Finance; Financial development; Economic growth; Economic development; Financial intermediation; Bank credit; Liquidity creation; Saving